2005
DOI: 10.1111/j.1365-2249.2005.02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological development of preterm infants in early infancy

Abstract: SummaryTo evaluate the immunological development of preterm infants, especially in early infancy, we examined the serum cytokine levels and the expression of Th2 and Th1 chemokine receptors, CCR4 and CCR5, on days 0, 14 and 28 in 16 low birth weight infants (1720·38 ± ± ± ± 502·80 g) born at less than 37 (33·63 ± ± ± ± 3·29) weeks of gestation. Using an enzyme-linked immunosorbent assay (ELISA), serum interleukin (IL)-4 levels exhibited an increase on day 14, but decreased to the initial level on day 28 ( P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…However, an increase in serum levels during the first weeks in preterm infants has been reported [31,32] . It has been speculated that this elevation is the second wave of inflammatory markers following the stimulus of an earlier first wave of inflammatory response or that it is a physiologically important signal for future T cell maturation and thereby important for the infant to prevent inappropriate immunological reactions resulting in an immature immune system.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in serum levels during the first weeks in preterm infants has been reported [31,32] . It has been speculated that this elevation is the second wave of inflammatory markers following the stimulus of an earlier first wave of inflammatory response or that it is a physiologically important signal for future T cell maturation and thereby important for the infant to prevent inappropriate immunological reactions resulting in an immature immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it also appears necessary to think of other end points than antibody concentrations to assess vaccine efficacy particularly in the elderly as also the cellular immune response may be impaired by the mechanisms of immunosenescence or due to underlying health conditions or immunosuppressive treatments for cancer, autoimmune disorders or chronic inflammatory conditions. Whereas most of the reasons for a low Th1 response in neonates and small infants are well understood [4,5,6], elderly persons have a high heterogeneity in their health states, and therefore a focus should be put on the exploration and restoration of the age-dependent immune dysregulation to improve immune functions. Thus, biomarkers of immunosenescence need to be defined which help to identify elderly persons in whom newly applied vaccines are likely to show low efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Th1-mediated responses, such as IFN-γ release and cytotoxicity, are developed soon after birth [4]. In preterm neonates, a higher susceptibility to viral infections was attributed to a relatively impaired IFN-γ production by γδ T cells within the first month of life [5].…”
Section: Age-associated Changes Of the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that the expression of CCR-5 was higher than that of CCR-4, suggesting an immunological shift toward Th1 cell types in the liver. Our previous study showed that the expression of CCR-4 mRNA develops after birth [25]. Higher expression of CCR-5 might indicate the immunological change in biliary atresia.…”
Section: Discussionmentioning
confidence: 98%